2015
DOI: 10.1016/j.msea.2015.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additional magnesium on mechanical and high-cycle fatigue properties of 6061-T6 alloy

Abstract: Abstract:The effect of additional solute magnesium (Mg) on mechanical and high-cycle-fatigue properties of 6061-T6 aluminum alloy is investigated in detail. By adding 0.5% and 0.8% Mg to the 6061-T6 alloy with a normal stoichiometric Mg 2 Si composition (base alloy), the alloy exhibits eminent strain-aging characteristics demonstrated by the emergence of serrated flow, the negative 2 strain-rate-sensitivity and relatively weakened temperature dependency of flow stress. The Mg-added new alloy also shows higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The fatigue properties of aluminum alloy joints play an important role in the safety and reliability of structural assemblies [ 6 ], with up to 90% of engineering constructions failing because of fatigue [ 7 ]. Researchers have found that excess solute Mg can improve the fatigue strength and fatigue life of 6xxx alloys [ 8 , 9 , 10 , 11 , 12 ]. Takahashi [ 9 ] reported that the fatigue strength and fatigue life of 6xxx alloys can be improved by adding excess Mg, so that Mg exists in solid solution in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue properties of aluminum alloy joints play an important role in the safety and reliability of structural assemblies [ 6 ], with up to 90% of engineering constructions failing because of fatigue [ 7 ]. Researchers have found that excess solute Mg can improve the fatigue strength and fatigue life of 6xxx alloys [ 8 , 9 , 10 , 11 , 12 ]. Takahashi [ 9 ] reported that the fatigue strength and fatigue life of 6xxx alloys can be improved by adding excess Mg, so that Mg exists in solid solution in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…With the fixed particle volume fraction of 20% and fixed particle number of 10, models with random and clustered particle distributions were created. In these where aluminum is matrix and silicon Carbide and Titanium Diboride are taken as reinforcement in these composites [11]. Figure 1…”
Section: Model Developmentmentioning
confidence: 99%
“…Aluminum as matrix material properties for the following matrix which it has shown very excellent in nature and possess light weight. The properties which are taken for the composites are Youngs modulus=75GPa, Poisson's ratio=0.3 and Yield stress= 250 N/m2 and similarly, Young's modulus = 410 GPa, and Poisson's ratio = 0.14 of silicon carbide as reinforcementand also Poisson's ratio is 0.15 and Youngs modulus is 430 GPa of titanium diboride is used as reinforcement can exhibit light weight to the structure [11][12], good resistance and increases the strength of the composite. After adding properties now, we must add section assignment to the matrix.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…The occurrence of strain-age hardening at a crack tip has been recognized to improve the non-propagation limit of fatigue cracking. For instance, solute Mg in Al alloys (Shikama et al 2012;Zeng et al 2012;Takahashi et al 2015) and solute carbon in steel (Li et al 2016(Li et al , 2017b(Li et al , 2018Kishida et al 2018), both of which trigger strain aging, significantly improve the K th of small crack growth. Figure 10.13 shows an example of the carbon effect on K th in steel.…”
Section: Strain-age Hardeningmentioning
confidence: 99%